Իրակությունների ընկալման հայեցակերպը և դրանց ոճական դրսևորումը (Չ. Դիքենսի «Օլիվեր Թվիստ»-ում) - Լուսինե Ավետիսյան (ՀՀ ԳԱԱ հրատ.)
Realia are known as material expressions of cultural life of the society. Realia are perceived in two ways- narrow and wide. According to narrow perception realia are defined as single units having no equivalents, that is why they are considered an “exotic” layer in the vocabulary of a language.
Keywords: Language and Literature